SALES ADMINISTRATION SYSTEM DESIGN MATERIALS AND CLOTHES ON PT. INDOTEX MENGGUNAKAN VISUAL BASIC 6.0 - Dedi Suryadi; Elly Agustina J. SKom, MMSI Elly Agustina J. SKom, MMSI (Jurnal Sistem Informasi, 2004)
PT. INDOTEX is a private company engaged in the textile industry which previouslyproduced material to make a T-Shirt, extends product garment (apparel).Sales system is an essential part of a company because it will determine the successof high and low sales gains. For the successful achievement of predetermined salestargets it needs a reliable supporter of sales administration.Finished goods sales administration system that is currently running between one partis not integrated with other parts. In addition there are several problems in dataprocessing, which does not comply with the hope and less assist management intaking decisions and the slow service. The author, trying to design a support systemadministration and apparel sales materials that can help solve the problems thatoccurred in the old system.